Uncovering a hidden diversity: two new species of Breviceps (Anura: Brevicipitidae) from northern KwaZulu-Natal, South Africa - Minter, Leslie R.; Netherlands, Edward C.; Preez, Louis H. Du (Zootaxa, 2017)
Breviceps carruthersi sp. nov. and Breviceps passmorei sp. nov. are described from northern KwaZulu-Natal. Both new species are distinguished from B. adspersus, B. mossambicus, B. poweri and B. cf. sopranus by substantial interspecific genetic divergence (> 6.8 uncorrected p-distance) in the mitochondrial 16S rRNA gene, differences in advertisement call structure and limited morphological variation. Breviceps carruthersi sp. nov. has a short, pulsatile call with minimal amplitude modulation and groups its calls. Breviceps passmorei sp. nov. differs significantly from B. adspersus and B. mossambicus in call duration and pulse number, but not in pulse rate or dominant frequency. For both new species morphological characters are of limited diagnostic value, necessitating a re-evaluation of the taxonomic status of populations currently assigned to B. adspersus and B. mossambicus in KwaZulu-Natal.